Science and Technology as New Curriculum in Salafiyah Pesantren to Response the Digital Challenges - Hasbi Indra, Yusuf Durachman, Nuraeni (International Journal of Advanced Science and Technology, 2020)
This paper studies the development of salafiyah pesantren (Salafiyah Islamic Boarding School) regarding their values, challenges, and responses through the educational curriculum. This education contributes to the national development through delivering knowledge for the younger generation. This generation lives in the digital 4.0 era, characterized by the use of technology such as controlling children’s activities through hand phone. The advancement in various fields in technology will cause human unemployment because the jobs are in robot’s hands. Besides, the development of technology information results in negative and positive effects, such as the competition amongst International or Asian Nations in the freedom of trade. Salafiyah pesantren has around 2 million santri (students) and more amounting, and 99 % just learn religious science such as Tafsir, Fiqh, Akhlak, Tauhid and so on throughout the classical text book (kitab kuning), the students (santri) do not learn general science, and the knowledge of Information and technology (IT). To face the challenges in this digital era, the students (santri) need to learn the knowledge in order that they possess good qualities to compete with each other. Therefore, the pesantren needs a curriculum to response to the competition in the world. This study discusses the development of salafiyah pesantren, the challenges in the Digital Age 4.0, and the response of the pesantren curriculum.